Genetic analysis of Agrobacterium tumefaciens unipolar polysaccharide production reveals complex integrated control of the motile‐to‐sessile switch. Issue 5 (29th July 2013) - Xu, Jing; Kim, Jinwoo; Koestler, Benjamin J.; Choi, Jeong‐Hyeon; Waters, Christopher M.; Fuqua, Clay
Summary Many bacteria colonize surfaces and transition to a sessile mode of growth. The plant pathogen Agrobacterium tumefaciens produces a unipolar polysaccharide (UPP) adhesin at single cell poles that contact surfaces. Here we report that elevated levels of the intracellular signal cyclic diguanosine monophosphate (c‐di‐GMP) lead to surface‐contact‐independent UPP production and a red colony phenotype due to production of UPP and the exopolysaccharide cellulose, when A. tumefaciens is incubated with the polysaccharide stain Congo Red. Transposon mutations with elevated Congo Red staining identified presumptive UPP‐negative regulators, mutants for which were hyperadherent, producing UPP irrespective of surface contact. Multiple independent mutations were obtained in visN and visR, activators of flagellar motility in A. tumefaciens, now found to inhibit UPP and cellulose production. Expression analysis in a visR mutant and isolation of suppressor mutations, identified three diguanylate cyclases inhibited by VisR. Null mutations for two of these genes decrease attachment and UPP production, but do not alter cellular c‐di‐GMP levels. However, analysis of catalytic site mutants revealed their GGDEF motifs are required to increase UPP production and surface attachment. Mutations in a specific presumptive c‐di‐GMP phosphodiesterase also elevate UPP production and attachment, consistent with c‐di‐GMP activation of surface‐dependent adhesin deployment.